Pengaruh Sistem Informasi Akuntansi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Padam Wair Pu’an Maumere Kabupaten Sikka - Kristina Natalia; Maria Nona Dince; Yoseph Darius P. Rangga (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to determine the Effect of Accounting Information Systems and Work Motivation on Employee Performance. This study used a quantitative approach, using primary data through questionnaires. The sampling technique uses the Slovin sample, where the determination of the sample is carried out and determined by dividing the population into several parts with a sample of 80 respondents. Data collection techniques using questionnaires were distributed to 80 respondents, where data analysis used multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS). Hypothesis testing is done through Test t and Test F. The results of the t test show that it shows that partially the Accounting Information System has no effect on employee performance. And UJi F partially shows that work motivation has a positive effect on employee performance.